2020
DOI: 10.32674/jis.v10i4.1042
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intercultural Exchange on Secondary School Exchange Students and Their Host Families

Abstract: The last decade has seen a significant increase of international student mobility and a growing popularity of secondary school exchange programs in the United States and around the world. Drawing upon culture learning theory, the purpose of this study is to understand the impacts, challenges, and rewards of intercultural exchange on secondary school exchange students and their host families. I performed a case study of in-depth interviews with six students who were placed in Hawai’i for an academic year on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In contrast to an Academic exchange program which is a form of educational exchange and mobility in which a student takes courses in a host university mainly with the aim of broadening and enhancing career choices and prospects and gaining job opportunities in the international job market (Parey and Waldinger, 2007, Teichler, 2007 as cited in González et al, 2010, p. 414;Gaia, 2015, p. 21;Biryuk, 2023), Cultural exchange programs provides students with not only the opportunity to learn about a different culture but also to integrate in it and experience it first-hand (Wang, 2013, p. 567;Hien, 2022, p. 151). However, both types of exchanges have been ever-increasing and encouraged as they result in great benefits for the host countries (Abreu et al, 2020, p.3;Sustarsic, 2020). Moreover, there has also been a great impact of cultural exchange on the tourism industry as these programs facilitate the travel of students and consequently the travel of their relatives and friends (López et al, 2016 as cited Abreu et al, 2020, p. 4).…”
Section: Cultural Exchangementioning
confidence: 99%
“…In contrast to an Academic exchange program which is a form of educational exchange and mobility in which a student takes courses in a host university mainly with the aim of broadening and enhancing career choices and prospects and gaining job opportunities in the international job market (Parey and Waldinger, 2007, Teichler, 2007 as cited in González et al, 2010, p. 414;Gaia, 2015, p. 21;Biryuk, 2023), Cultural exchange programs provides students with not only the opportunity to learn about a different culture but also to integrate in it and experience it first-hand (Wang, 2013, p. 567;Hien, 2022, p. 151). However, both types of exchanges have been ever-increasing and encouraged as they result in great benefits for the host countries (Abreu et al, 2020, p.3;Sustarsic, 2020). Moreover, there has also been a great impact of cultural exchange on the tourism industry as these programs facilitate the travel of students and consequently the travel of their relatives and friends (López et al, 2016 as cited Abreu et al, 2020, p. 4).…”
Section: Cultural Exchangementioning
confidence: 99%
“…Similarly, various studies (e.g., Berg et al, 2012;Huang et al, 2016;Suryanto et al, 2022) found out that engaging in interactive real-life situations during exchange provides students with enough opportunities to practice the language. In a more recent study, Sustarsic (2020) has revealed that some of the immediate impacts of cultural exchange include also enhanced English language skills. However, although these studies have been successful in highlighting one of the primary benefits of cultural and international exchange, there is a noticeable paucity in the level of activities opted for by students to improve their language skills and overall language…”
Section: Previous Studies On Foreign Language Learning Among Exchange...mentioning
confidence: 99%
“…Students also organize lecture schedules between the home campus and the destination campus for the student exchange program. In addition, it is related to sociocultural factors (Sustarsic, 2020). The use of different regional languages and often used spontaneously several times by both lecturers as teachers and students when communicating in class.…”
Section: Challenges Of Freedom Student Exchange Program Implementatio...mentioning
confidence: 99%